PERBANDINGAN PERAMALAN HASIL PRODUKSI IKAN MENGGUNAKAN METODE PERMULUSAN EKSPONENSIAL HOLT-WINTERS DAN ARIMA - RAHMAN, DIAN; SUMARJAYA, I WAYAN; SUKARSA, I KOMANG GDE (E-Jurnal Matematika, 2018)
Every year fish consumption in Indonesia always increases. Basis landing of fish (PPI) Kedonganan is one of the ports where the ship s docked and take part in economic activities of fisheries in Bali. T he aim of this study is to forecast the amount of fish production so that the fish production can be manage d . Some methods that can handle seasonal factors in time series forecasting includ e Holt-Winters exponential smoothing and ARIMA. The results show that ARIMA(2,0,4)×(3,1,2) 12 yields RMSE is 89 , 358 and MAPE is 0 . 81% whereas the value of fish outcomes prediction using Holt-Winters exponential smoothing method yields RMSE is 119 , 158 and MAPE is 1 . 14%.